POLYMER STABILIZED AMORPHOUS DISPERSIONS OF CLONAZEPAM: CHARACTERIZATION AND IN VITRO DISSOLUTION ANALYSIS - JAHAN, KHURSHID; BHOWMICK, TONMOY; FERDOUSI, JANNATUL; HOSSAIN, SHIHAB; SHUVO, NAHID HASAN (International Journal of Applied Pharmaceutics, 2026)
Objective: The objective of this study is to enhance the aqueous solubility and dissolution rate of poorly water soluble clonazepam (CLZ) by formulating polymer stabilized amorphous solid dispersions (ASDs) using melting and co-precipitation methods. The study systematically evaluates the effect of various hydrophilic polymers at different drug to polymer ratios on the physicochemical properties, dissolution behavior, and stability of the resulting solid dispersions (SDS). This research aims to optimize polymer selection and preparation techniques to improve the bioavailability and therapeutic efficacy of clonazepam, addressing current gaps in comparative studies of polymer based solubility enhancement strategies for this drug. Methods: SDS of CLZ were prepared using melting and co-precipitation methods with four hydrophilic polymers (HPMC K4MCR, PEG 6000, Methocel K15, and Kollidon Cl) at drug to polymer ratios of 1:1, 1:3, and 1:5. The formulations were characterized through in vitro dissolution studies, drug content analysis, and structural evaluations using Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), and Scanning Electron Microscopy (SEM). Results: The pure CLZ showed limited solubility (51±0.577%) at 60 min, whereas polymer ASDs significantly enhanced drug release. The PEG 6000 based formulation (ASD9, 1:5 ratio) exhibited the highest improvement (80.95±0.460%), followed by HPMC K4MCR (ASD3, 75.95±0.033%). Enhanced dissolution is attributed to increased carrier content and inhibition of crystallisation. FTIR and DSC analyses confirmed the absence of chemical interaction, while SEM demonstrated drug amorphisation, supporting improved solubility. ADMET analysis indicated the suitability of clonazepam for solubility enhancement via solid dispersion systems. Conclusion: Polymer stabilized ASDs improved the aqueous solubility and in vitro dissolution rate of CLZ. Among the polymers tested, PEG 6000 demonstrated the most favourable performance, improving drug release and stability without evidence of chemical interaction. These findings suggest that this approach may hold promise for enhancing the bioavailability and therapeutic efficacy of poorly water-soluble drugs, such as CLZ, although further in vivo studies are needed to confirm these effects.